A Romantic Relationship Perspective on Self-Injury in Young Adulthood - Caron, Angela (Université d'Ottawa / University of Ottawa, 2017)
Non-suicidal self-injury (referred to hereafter as self-injury) is considered a serious health concern among young adult populations, and is associated with a host of devastating physical and psychological consequences (Hasking, Momeni, Swannell, & Chia, 2008). Self-injury encompasses both thoughts of harming oneself in addition to acts of self-injury. Elevated lifetime prevalence rates of 13-17% suggest that self-injury is an issue of widespread nature, with reports indicating that a considerable proportion of young adults engage in self-injurious thoughts and behaviours (Nixon, Cloutier, & Jansson, 2008; Swannell, Martin, Page, Hasking, & St John, 2014; Whitlock, Eckenrode, & Silverman, 2006). Identifying the factors that precede self-injury is crucial to advancing current clinical conceptualizations and treatment strategies for those engaging in such thoughts and behaviours (Schenk, Noll, & Cassarly, 2010). Despite the recognized role of romantic relationship experiences in contributing to the functioning and adjustment of the individuals comprising the romantic dyad, very little empirical attention has been paid to examining whether dimensions of romantic relationships are linked to the use of self-injury. The present thesis, consisting of two independent studies, sought to provide a better understanding of the factors underlying this troubling phenomenon by examining links between dimensions of romantic relationships and self-injurious thoughts and behaviours among community-based young adults involved in couple relationships. The studies presented in the present thesis were approved by the University of Ottawa’s Research Ethics Board (see Appendix A for the Ethics Approval Certificate). The first study involved testing a novel conceptual model in which intimate partner violence victimization (i.e., physical, psychological, and sexual violence) was examined as a potential mediator of the relationship between child maltreatment (i.e., neglect; witnessing family violence; and physical, psychological, and sexual abuse) and self-injurious thoughts and behaviours. The sample consisted of 406 young adults (346 females; M = 19.87 years) who were involved in a couple relationship for a duration of at least six months at the time of participation. Results from bootstrapping procedures partially supported the theory put forth. Intimate partner violence victimization partially mediated the direct effect of child maltreatment on self-injurious behaviours. Contrary to predictions, intimate partner violence victimization did not mediate the association between child maltreatment and self-injurious thoughts. Hence, findings suggest that individuals who have experienced both forms of family violence may be particularly vulnerable to engaging in self-injurious behaviours. The second study comprised an investigation of the links between the three romantic behavioural systems (consisting of the attachment, caregiving, and sexual systems) and self-injurious thoughts and behaviours, and examined the incremental contributions of the systems in the prediction of young adult self-injury. The sample consisted of 255 young adults (223 females; Mage = 19.98 years) currently involved in a couple relationship. Linear discriminant analyses revealed that participants endorsing self-injurious thoughts experienced greater attachment anxiety and avoidance, controlling and compulsive romantic caregiving behaviours, and lower sexual satisfaction than did participants who did not endorse such thoughts. In contrast, findings indicated that the behavioural systems did not predict self-injurious behaviours. Such findings suggest that dimensions of the three interrelated behavioural systems hold unique roles in understanding young adult self-injurious thoughts, and that the constructs that predict self-injurious thoughts may differ from those that predict self-injurious behaviours.
Keywords: self-injury; romantic attachment; romantic relationships; intimate partner violence victimization